(untitled) (Revista Contexto & Educação, 2024)
This study is the result of a specialization course that aimed to analyse the conceptions of science teachers working in elementary school about meaningful learning, based on David Ausubel’s theory. The research consisted of a qualitative approach and as a methodological procedure a questionnaire was applied, organized into two blocks. The questions in block I made it possible to characterize the target audience of the research, while block II presented questions that emphasized the teachers’ understanding of meaningful learning, revealing their conceptions of the object under investigation. The answers were treated using content analysis, based on Bardin’s assumptions. The results of the research indicated that for this group of professionals, student learning occurs in a meaningful way when the teacher manages to arouse the student’s interest and curiosity by developing activities that stimulate and challenge them to seek solutions, making them a central element in the learning process. For these teachers, meaningful learning is linked to the contextualization of the content, i.e. the association of school knowledge with their lives. No relationship was identified between this type of learning and the students’ prior knowledge, which is one of the assumptions of the theory on which this work is based.